Computer programs to assist in high resolution thermal denaturation and circular dichroism studies on nucleic acids - Goodman, Thomas C. (1981)
Computer programs are described that direct the collection, processing, and graphical display of numerical data obtained from high resolution thermal denaturation (1-3) and circular dichroism (4) studies. Besides these specific applications, the programs may also be useful, either directly or as programming models, in other types of spectrophotometric studies employing computers, programming languages, or instruments similar to those described here (see Materials and Methods).